EVALUASI PERTUMBUHAN DAN HASIL SELEDRI (Apium graveolens,L.) PADA PERBEDAAN JENIS BAHAN DASAR DAN DOSIS PUPUK ORGANIK CAIR (The Evaluation of Celery (Apium graveolens, L.) Growth and Yield on Different Material and Doses of Organic Liquid fertilizers) - Made Deviani Duaja; . Neliyati; Hisar Tindaon (Bioplantae, 2012)
The research was conducted at Agriculture Researh Farm, Faculty ofAgriculture, Jambi University. The aim of this research were todetermine the effect of the combination of different material and dosesof organic liquid fertilizers on growth and yield of celery (Apiumgraveolens, L.). This research was designed using completelyrandomized block design (CRBD) with 7 treatments and 3 replications.The treatments were without organic fertilizers (P0d0), Bahan dasarlamtoro (Leucaena leococepahla) dengan dosis 15 ml/tanaman/4 hari(p1d1), Bahan dasar lamtoro (Leucaena leococepahla) dengan dosis 20ml/tanaman/4 hari (p1d2), Bahan dasar lamtoro (Leucaena leococepahla)dengan dosis 25 ml/tanaman/4 hari (p1d3), Bahan dasar kirinyuh(Cromolaena odorata) dengan dosis 15 ml/tanaman/4 hari (p2d1), Bahandasar kirinyuh (Cromolaena odorata) dengan dosis 20 ml/tanaman/4hari (p2d2), Bahan dasar kirinyuh (Cromolaena odorata) dengan dosis 25ml/tanaman/4 hari (p2d3), kontrol Pupuk NPK (16-16-16) dengan dosis6,25 g/tanaman.Keywords: celery, doses, liquid organic fertilizer, kirinyuh, lamtoro